Overdiagnosis: An unrecognised and growing worldwide problem in healthcare - Brodersen John (Sciendo, 2017)
Overdiagnosis is the diagnosis of deviations, abnormalities, risk factors, and pathologies that in themselves would never cause symptoms (this applies only to risk factors and pathology), would never lead to morbidity, and would never be the cause of death. Therefore, treating an overdiagnosed condition (deviation, abnormality, risk factor, pathology) cannot, by definition, improve the patient's prognosis, and can therefore only be harmful.